News and social media redefining journalism - Madhok, Madhuri (New Century Publications, 2015)
"Information is power and the basis of news. Every bit of news adds to our existing pool of knowledge. An informed nation is a strong nation. Knowledgeable and informed citizenry is the power house of a nation-state. A responsible citizen must be adequately informed about the local, national and international events to make rational choices. Any lacunae or distortion in information hampers the process of correct assessment and correct judgment. It is, therefore, imperative that no such flaw is allowed to affect the process of an informed and rational decision-making. Accurate, relevant and timely information is not just required for public alone. Even governments and many public and private bodies may also be in need of correct information. This book combines both theoretical aspects and practical insights that one would get from a class room lecture and personal interaction with professional peers. It is designed to help the budding journalists perfect the finer nuances of media writing"--Book jacket.